Screening of Potential Biosurfactant Producing Bacteria from Tanjung Perak Port, Surabaya - Susanti, Marlinda Elvina; Maftuch, Maftuch; Prihanto, Asep Awaludin (The Journal of Experimental Life Science, 2021)
Bacteria are bioremediation agents that are advised to overcome water pollution. This study aims to isolate biosurfactant-producing bacteria for bioremediation from Tanjung Perak Port, Surabaya. The isolates grown in specific media were tested for drop collapse, oil spreading test, and emulsification index. A total of 12 bacterial isolates were isolated from Tanjung Perak seawater contaminated with diesel oil. In the drop collapse test, four isolates had the highest positive score from this test, isolate LU-5, LU-7, LU-9, and LU-11. While in the second test, the oil spreading test, the highest positive score results were obtained in three isolates, isolates LU-2, LU-7, and LU-11. The emulsification index (E24) value showed that isolates LU-7, LU-9, and LU-11 were significantly higher than the others, which was above 10%. This study concludes that in Tanjung Perak, seawater-contaminated oil isolated several bacteria that produce biosurfactants, which have the potential to be developed as bioremediation agents.Keywords: bacteria, bioremediation, biosurfactant, diesel oil